Hijrah in the Sufisme Perspective: Study of Religious Phenomenology on the Role and Activities of Da'wah of Youth Hijrah in Cirebon - Atamimi, Abdul Basit; Muaz, Abdul; Handayani, Afni (Journal of Sufism and Psychotherapy, 2024)
This article aims to describe and analyze Islamic thinking about the phenomenon of Youth Hijrah in society. The term is used as an expression of the phenomenon of people who are new to or pay attention to Islam after paying little attention to it before. This research is aimed at answering how Islamic thoughts and views regarding Youth Hijrah, historical roots, the role, and da'wah activities of the Youth Hijrah are associated with the diversity of society in Cirebon. This research was conducted to find out, and analyze about; 1) Islamic thoughts and views on Youth Hijrah, 2) the Historical roots, role, and da'wah activities of Youth Hijrah in Cirebon, 3) The concept of religious phenomenology towards Youth Hijrah in Cirebon. The research approach used is qualitative. The method used is analytical descriptive. The results of this study are: First, Hijrah means "at-tarku", leaving something behind. Hijrah is essentially tarkul manhiyyat, leaving various religious prohibitions. Therefore, true migration is not limited to outward movements but also includes inner movements or changes. Second, the Youth Hijrah Phenomenon is a form of response among urban youth in responding to various social, economic, political, and technological changes associated with religious understanding. Third, the success of a religious movement is highly dependent on the community's affirmation of the discourse it echoes, especially in the Cirebon region, which has a very religious community.